Efforts to Overcome Community Diseases in Kampung Solok Village, Barus District, Central Tapanuli According to Criminology - Lubis, Junaidi; Indrayani, Leni; Suharno, Suharno; Maria, Juliya (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
The disease of society (guessing numbers) is one of the diseases that continues to exist to this day and is very difficult to overcome. From a legal perspective, social illness is a crime (delict) that is disturbing in society. The pattern of societal ills encourages people to always be lulled by momentary pleasures, causing some people to be lazy about carrying out business activities. Based on the research results, it is known that community disease is a community behavior that must continue to be addressed, because it has a negative impact on society. Law enforcement in dealing with community diseases, namely preventative management of community diseases, means that the response is carried out by preventing the spread of community diseases from becoming more widespread. In essence, this social disease is an act that is clearly contrary to legal, religious, moral and moral norms, and can endanger the survival of the community, nation and state.